2012
DOI: 10.1021/ol300740g
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Efficient Solid-Phase Preparation of Azido-peptides

Abstract: A shelf-stable and easily prepared diazotransfer reagent, imidazole-1-sulfonyl azide hydrochloride, was used to transform the N-terminus of a model peptide on solid phase into an azide moiety. It is demonstrated that this conversion was accomplished within 30 min with high efficiency under aqueous conditions on a NovaPEG resin or in DMF on polystyrene beads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…13 In brief, reduction of the corresponding Weinreb amide with DIBAL-H yielded the α-amino aldehyde, which was subjected in situ to a Seyferth-Gilbert homologation using the Bestmann-Ohira reagent. 20 The copperIJI)-catalyzed azide-alkyne cycloaddition (CuAAC; click chemistry) 21,22 was then performed with the resin-bound azide and the corresponding Fmoc-protected alkyne derivative using [(CH 3 CN) 4 Cu]PF 6 as a copper(I) source, and tris(benzyltriazolylmethyl)amine (TBTA) 23 as a stabilizing ligand. 10 1,2,3-Triazole containing peptides were built up on a Fmoc-Leu preloaded PEG-PS resin by standard SPPS up to the amide bond position to be replaced by an 1,2,3-triazole (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…13 In brief, reduction of the corresponding Weinreb amide with DIBAL-H yielded the α-amino aldehyde, which was subjected in situ to a Seyferth-Gilbert homologation using the Bestmann-Ohira reagent. 20 The copperIJI)-catalyzed azide-alkyne cycloaddition (CuAAC; click chemistry) 21,22 was then performed with the resin-bound azide and the corresponding Fmoc-protected alkyne derivative using [(CH 3 CN) 4 Cu]PF 6 as a copper(I) source, and tris(benzyltriazolylmethyl)amine (TBTA) 23 as a stabilizing ligand. 10 1,2,3-Triazole containing peptides were built up on a Fmoc-Leu preloaded PEG-PS resin by standard SPPS up to the amide bond position to be replaced by an 1,2,3-triazole (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Even if the isomers behave similarly,r egulatory affairs might be more complicated for ac linical transfer of the isomeric mixture.F urthermore, if applied for n-fold multimerization, for example, using polyazide scaffolds like DOTAZA (10) or TRAP(azide) 3 (11), SPAAC produces up to 2 n isomers, thus multiplying the impact of aforementioned concerns. Even if the isomers behave similarly,r egulatory affairs might be more complicated for ac linical transfer of the isomeric mixture.F urthermore, if applied for n-fold multimerization, for example, using polyazide scaffolds like DOTAZA (10) or TRAP(azide) 3 (11), SPAAC produces up to 2 n isomers, thus multiplying the impact of aforementioned concerns.…”
Section: Cu-free Click Chemistrymentioning
confidence: 99%
“…[8] It was found that strained alkynes,s uch as cyclooctyne, [9] can react under mild conditions with azides as well, giving rise to as et of reactions that are now termed strain-promoted azide-alkyne cycloadditions (SPAAC) or,m ore colloquially,c opper-free click chemistry.T o avoid confusion, it should be noted that the latter term is also widelyu sed for other click-style cycloadditionst hat are of similar value for bioconjugation purposes but rely on different mechanisms, such as the Diels-Alder reaction of aryltetrazines with strained dienophils like trans-cyclooctene or norbornene (see below,F igure 10). In addition, novel practical methods for synthesis of azide-o ra lkyne-decorated functional molecules are continuously being developed, [6] for example, the direct conversion of the N-terminus of ar esin-bound peptidei nto an azide, which provides facile access to clickablep eptides withoutt he necessity of coupling extra buildingb locks, [11] or the continuous synthesis of azides from primary amines by diazo transfer in ac opper-tubeflow reactor. Researchers nowadays have immediate access to an immensely large toolboxo fc lickable buildingb locks, greatlyf acilitating the rapid assembly of multifunctional constructs for biomedical applications or materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 5 was intended as the azide partner in the click chemistry reaction with the alkyne polymer 4. The azido functionality was introduced on the resin-bound peptide by converting its N-terminus from amino to azido by reaction with imidazole-1-sulfuryl azide hydrochloride, according to a published procedure applicable to all coded amino acids [27]. Peptide 6 was synthesised as a control peptide sequence for biological testing.…”
Section: Peg Derivatives For Multiple Conjugation Of Peptides By Azidmentioning
confidence: 99%